STUDI PERBANDINGAN KINERJA FREEZER 1/5PK DENGAN R134a DAN MUSICOOL (MC-134) - Heriyanto Rusmaryadi; Iskandar Badil (Jurnal Turbulen, 2019)
The purpose of this research is to design a freezer system that is used to study the comparison of the performance of a 1/5 PK freezer with the working fluid R-134a and Musicool MC-134. In this research, the main components used are 1/5 PK hermetic compressor, plate surface evaporator, water cooled condenser, and capillary pipes. The research was carried out by replacing R-134a refrigerant with Musicool MC-134 without changing the supporting components of the system (retrofit). The results showed that the retrofit from R-134a to Musicool MC-134 was very capable and feasible to be implemented. The system will be safe if the components of the system used are in accordance with the prerequisites (from the old working fluid, R-134a), the opposite will cause insecurity due to susceptibility to leakage (since the substitution of working fluid, MC-134, is more flammable). In addition, the use of MC-134 will result in a temperature drop that is much faster than R-134a, in other words "cooler faster" which is 30% faster (for a set point temperature of -18oC). Keywords: Retrofit, Musicool, R-134a, MC-134, Freezer